Image-Based Tool Characterization and DEM Simulation of Abrasive Brushing Processes - Anton Hoyer; Eckart Uhlmann (Machines, 2024)
Brushing with bonded abrasives is a finishing process used for deburring, edge rounding, and roughness reduction. However, due to the complex motion, chipping, and wear behavior of abrasive filaments, industrial brushing processes have historically relied on empirical knowledge. To gain a better understanding of filament interactions, a physical model based on the discrete element method was developed to simulate process forces and contact areas. Filament patterns of round brushes were determined through the use of laser line triangulation and image processing. These filament patterns showed interlocked filaments and yielded more accurate results when used in brushing simulations than the oversimplified square patterns, which were used in previous research. Simulation confirms the occurrence of filament interactions, distinguishes between sweeping and striking filament motions, and reveals dynamic behavior at high brushing velocities that may increase undesirable tool wear.